Treatment waste water of sugar industry with using of methane fermentation - Bublienko, Natalia; Semenova, Olena; Kulbachuk, O. (My University, 2012)
Characterized wastewater sugar industry. Proposed for their treatment using methane fermentation. This will clean the waste water by 95%. In the process of cleaning produced biogas with a high methane content.
Keywords: biogas; waste water; sugar plant; activated sludge; methane fermentation; біогаз; стічні води; цукровий завод; активний мул; метанова ферментація; биогаз; сточные воды; сахарный завод; активный ил; метановая ферментация; кафедра екології та екоменеджменту